ANALISIS PERHITUNGAN UTANG PAJAK PENGHASILAN PASAL 21 ATAS GAJI KARYAWAN DI KOPERASI BERKAH SAWIT NUSANTARA (BSN) DI KEC. POLEANG BARAT - Taufiq, Muh.; Triani, Neks; Nichen, Nichen (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the calculation of Income Tax Article 21 liabilities on employee salaries at the Berkah Sawit Nusantara (BSN) Cooperative in Poleang Barat District. The main focus of the research is to determine the extent to which the cooperative has fulfilled its tax obligations on employee income, including holiday allowances (THR) and bonuses. The results show that throughout 2024, BSN Cooperative did not withhold or report Income Tax Article 21 on employee earnings. This was due to the treasurer’s lack of understanding of tax regulations and the absence of dedicated tax personnel. As a result of this negligence, the cooperative received warnings and is at risk of being sanctioned by the tax authority, with tax liabilities that have not yet been accurately calculated. The study also reveals that the cooperative lacks an adequate tax management and recording system. Therefore, improving human resource competencies through tax training and technical consultations with relevant parties is essential. The study concludes that BSN Cooperative must improve its tax administration and enhance the treasurer’s understanding of tax obligations in order to comply with prevailing regulations professionally. Keywords: Income Tax Article 21, Employee Salaries, BSN Cooperative